APPLICATION OF CLEANER PRODUCTION OPPORTUNITIES IN TAFU INDUSTRY CENTRE IN KALISARI AND CIKEMBULAN VILLAGE, BANYUMAS DISTRICT, PURWOKERTO - Lestario Widodo (BPPT)
Cikembulan and Kalisari village, in Banyumas district of Central Java, has grown into TOFU industrial center. The population of tofu industrial is about 600 industry, spread across two villages. Livelihoods of local people are farmers and traders to support the industrial activities of tofu, soy such as providing raw material to provide firewood for cooking, and providing simple tools, etc.. In the process of production, tofu waste industry, one of which liquid waste is usually dumped directly into rivers or drains around the house, so the environment becomes polluted. The purpose of this activity is to provide cleaner production training and technical assistance in the process of cooking. The results showed that with improved stoves and furnaces, the fuel consumption of 42.5% save, or save Rp 31 453,-per period of the process, the length of cooking know that 50% faster. Break Even Point (BEP) The value of the dimension of time is 191 days, and the improvement of environmental conditions.keywords : cleaner production, tofu waste industry